Winter / satire myth in İncili Çavuş anecdotes - Şenocak, Ebru; Alsaç, Fevziye (Milli Folklor Dergisi, 2020)
The anecdotes are texts based on narration that include humor, wit, criticism and satire in structure and aim to make people laugh and think at the same time. The anecdote type has a point of view that reveals the universe of thought, experience and culture of society; it symbolizes the values of society in which it belongs. Messages in the anecdotes are expressed through a type created by the community, which provides the repre-sentation of the event or situation. The situation or the person who is criticized in the content presented through the type that represents life and the ideals of society is satiated with an ironic language. The narrative made to show the truth in anecdotes that are short narratives is a moral setting given a concise message in the face of criticized behavior / person / situation. Myth systematics is a parallelism theory between the seasons and literary genres developed by Northrop Frye. This theory studies a symbolic relationship between the nature-dependent cycles of the seasons and the literary genres, which are the artistic creations of man. The comedy genre is reborn, in spring and the romance type is the theme of happiness, with summer season. The tragedy is the sad fall of the autumn and the satire is the theme of the defeat of the challenging winter season. The myth of satire that meets the winter cycle, which is one of the four seasons cycles, merges with the critical meaning, comic expression and irony of the anecdotes. The moral criterion of the winter / satire myth and the jargon is that it is an example of the satire of the pleasure of the person / society. In the seasonal cycle, the content of the text becomes important as in the winter / satire myth. The winter / satire myth is a method of criticism created by a symbolic language that includes the defeat of opposing thought or the world of persons, with ironic prejudice. The situation / person / event that is criticized in the paragraph text is treated with the theme of the defeat of the winter myth with ironic language and humor. The hard life struggle of the winter season is the myth of the struggle between people / communities in the form of dual contrast with humor. Satire is based on the principle of morality and gratification; the moral criterion turns into pleasure created by social values and judgments. In the anecdotes, the striking message, which is shaped and thought by the cultural identity, reveals the defeat of the myth of winter / satire against the opposing power through the anecdote type. In İncili Çavuş anecdotes, the inter-communal struggle, the misconduct of the ruling class, and the attitudes of the people in the society are criticized by the moral values of the satire myth. The struggle between the societies as a feature of the period in the İncili Çavuş anecdotes is exemplified in Acem and French societies, which have an important place in the bilateral relations of Ottoman society. The wickedness of the ruling class with its defeat of the winter myth and the unqualified and cruelty of the ruling class disrupts the social order. By consuming the answers of opposing power, which is criticized by the type of wisely of the anecdote type, it transmits the striking message of the winter cycle as a code. In this study, the winter / satire myth was introduced from the seasonal cycles used in the study of literary genres and the content of the anecdote in terms of winter / satire myth was discussed. As an example of this situation, the İncili Çavuş anecdotes have been selected. His personality and anecdotes that exemplify the social, political and cultural life of the period have been evaluated. Based on the winter / satire myth, the anecdotes of the period which exemplify the mentality of the era with the political and social messages of the Incili Cavus have been interpreted. © 2020, Milli Folklor Dergisi. All rights reserved.
İncili çavuş fikralarinda kiş/taşlama miti
Keywords: Anecdote; Irony; Winter /satire myth; İncili Çavuş